Analysis of Incomplete Medical Record Filling in Indonesia - Irma Binarti; Febry Dulfi Fitriyana (International Journal of Science and Society, 2022)
Incomplete medical records are an obstacle in obtaining quality medical records. Using a literature review approach sourced from various journals and research in Indonesia, this study aims to obtain an overview of the interrelationships of multiple factors that influence the incomplete filling of medical records in hospitals in Indonesia. Based on the results of the study, it can be seen that there are two interrelated areas of improvement that need to be paid attention to by Health facilities in ensuring the quality of medical record recording, including areas for improving the quality of human resources (Man and Machine factors); quality standard compliance area (Method and Material Factors). The fulfillment of these two areas of improvement depends on the commitment of Health Facilities to prioritize the improvement of these two areas in the budget (money factor).